On the wings of time : Rome, the Incas, Spain, and Peru - MacCormack, Sabine (Princeton : Princeton University Press, 2007)
Historians have long recognized that the classical heritage of ancient Rome contributed to the development of a vibrant society in Spanish South America, but was the impact a one-way street? Although the Spanish destruction of the Incan empire changed the Andes forever, the civil society that did emerge was not the result of Andeans and Creoles passively absorbing the wisdom of ancient Rome. Rather, Sabine MacCormack proposes that civil society was born of the intellectual endeavors that commenced with the invasion itself, as the invaders sought to understand an array of cultures. Looking at the sixteenth- and seventeenth-century people who wrote about the Andean region that became Peru, MacCormack reveals how the lens of Rome had a profound influence on Spanish understanding of the Incan empire.--Publisher description.
Universals and particulars : themes and persons -- Writing and the pursuit of origins -- Conquest, civil war, and political life -- The emergence of patria : cities and the law -- Works of nature and works of free will -- "The discourse of my life" : what language can do -- The Incas, Rome, and Peru -- Epilogue: Ancient texts : prophecies and predictions, causes and judgments.
Includes bibliographical references (pages 275-310) and index.
Print version record.
English.
JSTOR
Keywords: Incas -- Historiography; Incas -- First contact with other peoples; Incas in literature -- History and criticism; Indian literature -- Andes Region -- History and criticism; Spanish literature -- Andes Region -- History and criticism; Peru -- History -- Conquest, 1522-1548.; Incas -- Historiographie; Incas -- Premiers contacts avec d'autres peuples; Incas dans la littérature -- Histoire et critique; Pérou -- Histoire -- 1522-1548 (Conquête); Incas -- First contact with other peoples; Incas -- Historiography; Incas in literature; Indian literature; Spanish literature; Andes Region; Peru; Spanjaarden; Cultuurcontact; Latijns-Amerika.; 1522-1548; Aeneid; Alcalde; Alfonso X of Castile; Americas; Amun; Ancient Rome; Andean civilizations; Andes; Arrival and Departure; Aspromonte; Atahualpa; Ataulf; Atoll; Bartolomé de las Casas; Caesar and Pompey; Caprera; Cesarea; Chronology; Circumnavigation; Classical antiquity; Classical tradition; Clime; Coat of arms; Conquistador; Coral reef; Cusco; Decree; Deity; Diego de Almagro; Djed; Edict; Edmundo O'Gorman.; Expedition of the Thousand; Francisco Pizarro; Francisco de Vitoria; Friar; From Time Immemorial; Frontier; Future